2015
DOI: 10.1073/pnas.1419533112
|View full text |Cite
|
Sign up to set email alerts
|

Targeted ablation of cholinergic interneurons in the dorsolateral striatum produces behavioral manifestations of Tourette syndrome

Abstract: Gilles de la Tourette syndrome (TS) is characterized by tics, which are transiently worsened by stress, acute administration of dopaminergic drugs, and by subtle deficits in motor coordination and sensorimotor gating. It represents the most severe end of a spectrum of tic disorders that, in aggregate, affect ∼5% of the population. Available treatments are frequently inadequate, and the pathophysiology is poorly understood. Postmortem studies have revealed a reduction in specific striatal interneurons, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
175
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(188 citation statements)
references
References 61 publications
12
175
1
Order By: Relevance
“…1E,F). Previous studies have used selective expression of DTR as a method for killing populations of neurons defined by their neurochemical phenotype or spatial location (Gropp et al, 2005;Carter et al, 2013;Xu et al, 2015). Our methodology expands on previous techniques to ablate neurons in a structure that project to a distinct target site, thereby killing these neurons in a directionally specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…1E,F). Previous studies have used selective expression of DTR as a method for killing populations of neurons defined by their neurochemical phenotype or spatial location (Gropp et al, 2005;Carter et al, 2013;Xu et al, 2015). Our methodology expands on previous techniques to ablate neurons in a structure that project to a distinct target site, thereby killing these neurons in a directionally specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem studies have shown a decrease in choline acetyltransferase containing striatal interneurons, supporting reports of an anatomical reduction of cholinergic interneurons 15 . In mice, ablation of 50% of cholinergic interneurons in the dorsomedial striatum caused no effect, whereas ablation in the dorsolateral striatum plus a stressful stimuli or amphetamine challenge caused tic-like stereotypic behaviours 29 . Striatal cholinergic interneurons may coopt dopamine terminals and drive GABA release 30 .…”
Section: Acetylcholinementioning
confidence: 98%
“…At the November, 2014, annual meeting of the Society for Neuroscience, Xu et al presented evidence that removing about half of the cholinergic interneurons in the dorsolateral striatum reproduced some features of TS in a rodent model 9 ; see also 10 . This model was inspired by the fascinating autopsy studies that found decreased numbers of striatal interneurons in Tourette syndrome 11 .…”
Section: Resultsmentioning
confidence: 99%